Mitigation of drought stress in eggplant by date straw and plastic mulches - Majid Amiri Rodan; Mohammad Reza Hassandokht; Davoud Sadeghzadeh-Ahari; Amir Mousavi (Journal of the Saudi Society of Agricultural Sciences)
Eggplant (Solanum melongena L.) is an important vegetative crop, which grow in the different parts of Iran. It is well-known for drought tolerance, but the quality and quantity of the plant suffer from severe water deficit. The current study objected to evaluate the effects of date straw and plastic mulches on biochemical, physiology, and quality characters in eggplant under water deficit. The experiment was performed as a split-split plot based on randomized complete block design (RCBD) with three replications in Rodan, Hormozgan, Iran. The studied factors including crop water requirement at three levels (40, 70, and 100%), date straw mulch at two levels including control and date straw mulch, and plastic mulch at three soil depths (0, 100, and 120 cm), which were distributed in the main, sub, and sub-sub plots, respectively. ANOVA illustrated that the triple- interaction effects of the three studied factors were statically significant on the measured characters (P < 0.05 or P < 0.01), except for malondialdehyde and vitamin C. According to the results of present study, carotenoids, fruit weight, protein content, and total soluble solids were decreased, while the rest measured characters were increased, under the water deficit. In addition, the results revealed that the application of the date straw and plastic mulches mitigated the adverse effects of water deficit. Our results revealed that applying the date straw mulch with plastic mulch at 120 cm of soil depth could be more efficient to reduce the negative effects of water stress on eggplant, compared to other treatments.